The instrumentalization of the Law through the use of the Legal domain: A theoretical approach - Fonseca Lindez, Ignacio; Miró Colmenárez, Pablo Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The instrumentalization of the Law, through the use of the legal and the information domains, is at the centre of many of the strategies currently used by Russia and China to achieve their strategic objectives in their International Relations. The study focuses on describing the different existing doctrines on the instrumentalization of the Law and the Infromation domain and develops, from a theoretical perspective, the evolution of the Western vision of lawfare, the russian version based on the Maskirovka doctrine and the chinese approach to its falu zhan concept.